Kategoria braku odpowiedzi w świadomości rozmówców - Lapis, Włodzimierz (Investigationes Linguisticae, 2007)
The article presents the analysis of utterances found on Polish Internet sites concerning lack of reply: what is it, what does it tell us, and what logical value does it have? The result of this work is the introduction of reliable criteria, enabling us to give correct replies in a given situation.